The role of ring current particle injections: Global simulations and Van Allen Probes observations during 17 March 2013 storm. Issue 4 (22nd February 2014) - Yu, Yiqun; Jordanova, Vania; Welling, Dan; Larsen, Brian; Claudepierre, Seth G.; Kletzing, Craig
<x xml:space="preserve">Abstract</x> We simulate substorm injections observed by the Van Allen Probes during the 17 March 2013 storm using a self‐consistent coupling between the ring current model RAM‐SCB and the global MHD model BATS‐R‐US. This is a significant advancement compared to previous studies that used artificially imposed electromagnetic field pulses to mimic substorm dipolarization and associated inductive electric field. Several substorm dipolarizations and injections are reproduced in the MHD model, in agreement with the timing of shape changes in the AE/AL index. The associated inductive electric field transports plasma sheet plasma to geostationary altitudes, providing the boundary plasma source to the ring current model. It is found that impulsive plasma sheet injections, together with a large‐scale convection electric field, are necessary to develop a strong ring current. Comparisons with Van Allen Probes observations show that our model reasonably well captures dispersed electron injections and the global Dst index.